Se o senhor não tá lembrado, dá licença de contá: uma abordagem discursiva da experiência de desapropriação - Santos, Paula Perin dos (2019)
The Rodoanel Mário Covas is an expressway in the final phase of construction around the Metropolitan Region of São Paulo. Thousands of families who lived in areas of the route were expropriated for the construction of this expressway, especially the residents of Estancia Jaraguá, a neighborhood located in the subdistrict of Parada de Taipas in São Paulo, the capital of São Paulo. In face, this thesis aims to analyze life stories about the expropriation experience, through Phenomenological Interpretative Analysis and Discursive Semiotics, in order to categorize the discourse of the expropriated. We have chosen three specific objectives, which are: a) To analyze the discursive categories underlying the expropriation experience; b) To investigate the representations of the self/enunciator in relation to objects of positive or negative value with which they are confronted; c) To categorize the expropriation discourse. It is a qualitative research, which uses the Interpretative Phenomenological Analysis (SMITH; OSBORN, 2003) and Ethnosociology (BERTAUX, 2010) for an inductive approach to life narratives, in order to define the discursive categories present in such texts. We have adopted the contributions of the Discursive Semiotics (BARROS, 2002; FIORIN, 2011), of the life narrative studies (MAIA-VASCONCELOS, 2011; PINEAU; LEGRAND, 2012; DELORY-MOMBERGER, 2014; BRUNER, 2014; FERRAROTI, 2014), of existential spaces and the senses of place and non-places (CERTEAU, 1998; AUGÉ, 2012; PALLASMAA, 2013; BERGSON, 2013; HALL, 2014; REIS, 2017) as a theoretical contribution. In this study, we observe three discursive categories of the experience of being expropriated, represented by three enunciateurs: the deterritorialized enunciator, the territorialized enunciator and the multiterritorialized enunciator. The deterritorialized enunciator, dispossessed of the place from which he felt he belonged, starts to live on memories. This condition implies the rejection of everything that relates to the present house. His life story is built on the premise that the there (previous house) was better than the here (current house). The territorialized enunciator does not feel that he belongs to the previous house, so being expropriated is the means by which he acquires the necessary resources to buy the house he wants. His life history is built on the premise that the there (previous house) was bad, but the here (current house) is much better. For this reason, territorialized enunciator feels that he belongs to the new house. Difficulties faced during the process are interpreted as part of a larger plan for the acquisition of the dream house. Finally, the multiterritorialized enunciator does not show emotional attachment to the existential place: neither to the previous house, nor to the current house, but to the ease of access to urban life that this property can provide. His life history is built from the premise that the there (previous house) was dangerous, but the here (current house) is safe and "close to everything". By opting for no place, a term that designates circulation spaces, crossing points, the multiterritorialized enunciator renounces the feeling of belonging to a territory, preferring not to cling to a residence to be close to everything. He prefers easy passage and the freedom to come and go, rather than resigning himself to the distance of the great centres, to the margins of social life that allows us urbanity.